2019
DOI: 10.1093/ajcn/nqy376
|View full text |Cite
|
Sign up to set email alerts
|

Prebiotics in irritable bowel syndrome and other functional bowel disorders in adults: a systematic review and meta-analysis of randomized controlled trials

Abstract: Background Irritable bowel syndrome (IBS) and other functional bowel disorders (FBDs) are prevalent disorders with altered microbiota. Prebiotics positively augment gut microbiota and may offer therapeutic potential. Objectives The aim of this study was to investigate the effect of prebiotics compared with placebo on global response, gastrointestinal symptoms, quality of life (QoL), and gut microbiota, via systematic review a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
82
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(85 citation statements)
references
References 53 publications
1
82
1
1
Order By: Relevance
“…However, sensitivity analyses revealed that prebiotic doses of ≤6 g/d improved flatulence (SMD 0.35, 95% CI −0.71‐0.00, P = .005), whereas higher doses did not. Flatulence was significantly exacerbated with inulin‐type fructans (SMD 0.85, 95% CI 0.23‐1.47, P = .007), but was improved with non‐inulin‐type fructans (SMD −0.34, 95% CI −0.66 to −0.01, P = .04) 36 . These findings highlight the importance of considering both the type and the doses of prebiotics in clinical practice and research.…”
Section: Food Supplementsmentioning
confidence: 84%
See 1 more Smart Citation
“…However, sensitivity analyses revealed that prebiotic doses of ≤6 g/d improved flatulence (SMD 0.35, 95% CI −0.71‐0.00, P = .005), whereas higher doses did not. Flatulence was significantly exacerbated with inulin‐type fructans (SMD 0.85, 95% CI 0.23‐1.47, P = .007), but was improved with non‐inulin‐type fructans (SMD −0.34, 95% CI −0.66 to −0.01, P = .04) 36 . These findings highlight the importance of considering both the type and the doses of prebiotics in clinical practice and research.…”
Section: Food Supplementsmentioning
confidence: 84%
“…With the gut microbiota suggested to contribute to the pathophysiology of IBS, studies have also investigated the impact of prebiotic fibers, which are “selectively utilized by host microorganisms conferring a health benefit” 35 . A recent systematic review and meta‐analysis of 11 RCTs in 729 patients with IBS and other functional bowel disorders showed that although prebiotics increased bifidobacteria compared to placebo (mean difference 1.16 log10 rRNA copies, 95% CI 0.06‐2.26, P = .004), there were no differences in response to treatment, abdominal pain, bloating, and flatulence 36 . However, sensitivity analyses revealed that prebiotic doses of ≤6 g/d improved flatulence (SMD 0.35, 95% CI −0.71‐0.00, P = .005), whereas higher doses did not.…”
Section: Food Supplementsmentioning
confidence: 99%
“…In contrast, an improvement in symptoms with FOS was reported in a more recent RCT, in which 105 patients diagnosed with minor Functional Bowel Disorders were randomized into two groups to receive either 5 g/day of short-chain FOS or 5 g of a placebo (sucrose and maltodextrins) over a 6-week period [122]. Despite these data, evidence of prebiotic effectiveness in adult IBS patients is still controversial, as reported in a recent systematic review and meta-analysis of randomized controlled trials, in which the prebiotic type and dose significantly influenced symptom improvement and exacerbation [123]. As a matter of fact, there is some evidence that higher doses may have a negative effect on symptoms [120,121,[124][125][126].…”
Section: Prebiotics and Gastrointestinal Disordersmentioning
confidence: 99%
“…Indeed, several clinical studies have examined prebiotics' performance in ameliorating symptoms of functional bowel disorders. A handful of RCTs evaluating the efficacy and safety of prebiotics in IBS [67,68] have been performed. In 1999, a small, double-blind crossover trial of oligofructose published by Hunter and colleagues [69] showed no therapeutic value in IBS patients.…”
Section: Prebioticsmentioning
confidence: 99%